1993
DOI: 10.1192/s0007125000292623
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Medication in the Maintenance Treatment of Schizophrenia and its Conceptual Implications

Abstract: Beyond the continuing use of neuroleptic medication, psychopharmacological treatment approaches during the maintenance phase of schizophrenia often involve adjunctive medication. Appropriate use of such ‘polypharmacy’ can be crucial to patients in achieving their optimal levels of symptom management and functional capacity, although the risks of side-effects and medication interactions must be weighed. This paper reviews the use of adjunctive anti-Parkinsonian medication, benzodiazepines, propranolol, antidepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 128 publications
0
25
0
Order By: Relevance
“…7 Second, tricyclic antidepressants, which are equally effective antidepressants, do not improve negative symptoms in schizophrenic patients, although they can be useful when depression is associated with the disease. 35 Notably, SSRIs (which acts through serotonergic receptors), but not maprotiline (which acts via noradrenergic receptors), are effective augmentation agents for negative symptoms, 12 which suggests that the mechanism requires modification of the serotonergic system. 35 Paradoxically, clozapine and fluvoxamine-haloperidol combination produce a similar clinical effect, despite their different pharmacology: clozapine is a 5-HT antagonist and fluvoxamine elevates 5-HT concentration.…”
Section: Selective Serotonin Reuptake Inhibitor-antipsychotic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…7 Second, tricyclic antidepressants, which are equally effective antidepressants, do not improve negative symptoms in schizophrenic patients, although they can be useful when depression is associated with the disease. 35 Notably, SSRIs (which acts through serotonergic receptors), but not maprotiline (which acts via noradrenergic receptors), are effective augmentation agents for negative symptoms, 12 which suggests that the mechanism requires modification of the serotonergic system. 35 Paradoxically, clozapine and fluvoxamine-haloperidol combination produce a similar clinical effect, despite their different pharmacology: clozapine is a 5-HT antagonist and fluvoxamine elevates 5-HT concentration.…”
Section: Selective Serotonin Reuptake Inhibitor-antipsychotic Therapymentioning
confidence: 99%
“…35 Notably, SSRIs (which acts through serotonergic receptors), but not maprotiline (which acts via noradrenergic receptors), are effective augmentation agents for negative symptoms, 12 which suggests that the mechanism requires modification of the serotonergic system. 35 Paradoxically, clozapine and fluvoxamine-haloperidol combination produce a similar clinical effect, despite their different pharmacology: clozapine is a 5-HT antagonist and fluvoxamine elevates 5-HT concentration. Furthermore, adding SSRI to clozapine may improve effectiveness.…”
Section: Selective Serotonin Reuptake Inhibitor-antipsychotic Therapymentioning
confidence: 99%
“…Meanwhile, the in vitro study by von Moltke et al (1994) has shown that ketoconazole, an inhibitor of CYP3A4 (Olkkola et al 1994;Watkins 1994), inhibits the 4-and ␣ -hydroxylation of alprazolam, suggesting that alprazolam is metabolized by CYP3A4. Furthermore, Yasui et al (1996) have reported that erythromycin, an inhibitor of CYP3A4 (Olkkola et al 1993;Watkins 1994) Carbamazepine has been used increasingly in the treatment of psychiatric disorders (Siris 1993;Post et al 1994;Otani et al 1996a). However, it has been suggested that carbamazepine induces the metabolism of several psychotropic drugs (Arana et al 1986;Backman et al 1996;Otani et al 1996b;1997b) by a not fully characterized enzyme induction.…”
mentioning
confidence: 99%
“…Carbamazepine has been used increasingly in the treatment of psychiatric disorders (Siris 1993;Post et al 1994;Otani et al 1996a). However, it has been suggested that carbamazepine induces the metabolism of several psychotropic drugs (Arana et al 1986;Backman et al 1996;Otani et al 1996b;1997b) by a not fully characterized enzyme induction.…”
mentioning
confidence: 99%
“…Lithium has been shown to benefit up to half of all patients (Siris, 1993).Predictors of response to lithium include affective symptoms, aggression and family history of affective disorder; improve ments are not limited to predictor symptoms. Benzodiazepines are likely to be helpful when psychosis is accompanied by marked anxiety, or to control behaviour disturbance in acute relapse.…”
Section: Differential Diagnoses and Simple Solutionsmentioning
confidence: 99%